2019
DOI: 10.1186/s40463-019-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating short and long term outcomes following pediatric Myringoplasty with Gelfoam graft for tympanic membrane perforation following ventilation tube insertion

Abstract: Background Myringotomy with ventilation tube (VT) insertion to treat recurrent acute otitis media and chronic secretory otitis media has become one of the most common surgical procedures performed in children. Although contemporary literature has detailed the various patient and perioperative factors that affect successful pediatric myringoplasty, there is still limited evidence surrounding the increasing number of graft material options. In particular, gelfoam patching has arisen as a simple and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Common graft materials are cartilage, perichondrium, temporalis fascia, and fat. Some biological materials are used to repair chronic perforations [1][2][3][4][5]. The regenerative effects of basic fibroblast growth fac-tor (bFGF) on the TM are striking.…”
Section: Introductionmentioning
confidence: 99%
“…Common graft materials are cartilage, perichondrium, temporalis fascia, and fat. Some biological materials are used to repair chronic perforations [1][2][3][4][5]. The regenerative effects of basic fibroblast growth fac-tor (bFGF) on the TM are striking.…”
Section: Introductionmentioning
confidence: 99%
“…(TF). Song et al [ 1 ] recently published a paper entitled: “Evaluating short and long term outcomes following pediatric myringoplasty with gelfoam graft for tympanic membrane perforation following ventilation tube insertion.” The cited authors performed gelfoam myringoplasty to treat TMPs following VT insertion. In this technique, small amount of blood was absorbed into the gelfoam to create a little ‘blood patch’.…”
mentioning
confidence: 99%
“…The authors reported that, at initial follow-up, 90.6% of the gelfoam (GF) group exhibited successful TM closure, compared to 50% of the HA, 85.7% of the TC, and 66.7% of the TF groups in this study [ 1 ]. The gelfoam alone was superior to HA, TC, and TF.…”
mentioning
confidence: 99%
See 2 more Smart Citations